Value Priorities of Public and Private University Students - Mehmet Fatih Yigit (Research in Social Sciences and Technology- OpenED Network, 2017)
In this study, the aim of the study is to find out whether there is a statistically significant difference between value priorities of public and private universities in Turkey. This is a quantitative study using ANOVA for the analysis of the data. The results suggest that private university students show greater tendency towards universalism, power, tradition, conformity, and hedonism compared to the public university students, while the public university students showed greater sensitivity to benevolence compared to the private university students. The test results also showed that the education level of mothers do not have a significant effect on value priorities of both public and private university students, while father's education has significant effect on the perception of power.